Public Responses to The Customs Official Twitter Account's Posts: Pragmatic Approach - Daniel Fernando Siahaan; Diendra Wahyu; Fabian Putra Nazreensyah; Dian Marisha Putri (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
The article explores the public's response to Indonesia’s Customs official Twitter account. The research uses a qualitative approach, focusing on content analysis methods. This research also utilizing the speech act theory, with a focus on illocutionary acts. The research data was collected by screenshots of 25 responses on Twitter. The analysis revealed that the responses were predominantly directive acts (8 responses), followed by expressive acts (6), declarative acts (5), representative acts (4), and commissive acts (2). The predominance of directive acts indicates that many responses aimed to influence others to boycott the customs agency, reflecting a strong public sentiment against the institution. This study also highlights the critical nature of social media interactions with government agencies and underlines the need for improved public engagement strategies. We hoping the results of this research can provide deeper understanding into the dynamics of communication between government institutions and the public via social media and its implications for public acceptance and perception.